A survey to determine the prevalence of Theileria spp. in beef cattle in the northern tablelands of New South Wales. Issue 10 (23rd September 2013) - Biddle, A; Eastwood, S; Martin, L; Freeman, P; Druce, E
<x xml:space="preserve">Abstract</x> Objective To estimate the within and between herd prevalences for Theileria orientalis in beef herds in the eastern section of the New England Livestock Health and Pest Authority. Design Stratified random survey. Methods From each of 46 randomly selected beef cattle herds, 10 cattle were randomly selected and blood sampled. Packed cell volumes (PCV) were calculated and the number of Theileria organisms in blood smears was counted. Within‐herd results were grouped into zero, low, medium or high prevalence based on the number of positive smears. A questionnaire was completed by the farmer at the time of sampling and responses to variables such as farm location and management strategies were compared with the laboratory findings. Results Theileria species at varied levels on smears were found in 33 of the 46 herds sampled, which gave a herd prevalence of 72% for this study. Approximately 18% of herds were in the medium or high prevalence group. Half of the properties reported tick activity and 70% of those used tick control. Conclusions The 72% herd prevalence of Theileria spp. found in this study shows that infection is widespread in beef herds in the northern tablelands of New South Wales. Although 82% of the sampled herds had low or zero within‐herd prevalence estimates, a significant number of herds had medium or high levels of Theileria. The risk factor questionnaire has provided some associations, such as the link between tick treatment and Theileria detection, that require more targeted studies.